The Study of Speech Acts in Online Discussion Study of ELT Classroom - Madina, Sarah (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2022)
This present study deals with the classification of speech acts produced by the students in an online discussion study of English department students at State University of Padang, Indonesia. This study is carried out by using a qualitative approach that describes the use of students speech acts in the interaction of student-student, and student-lecture. 24 students engaged in the discussion study and participated as the source of the data. The instrument used by the researcher to collect the data was an observation sheet supported by video recording. The recording of the video was transcribed into a text which to examined by the researcher of their speech acts. The research findings show that there were assertive, directives, expressive, and commissives performed by English department students. The most frequent speech acts performed by the students were assertive with a total of 7 utterances, directive with a total of 9 utterances, and commissive with a total 0f 10 utterances. Assertive speech acts were performed to demonstrate the material of the discussion by the presenter and used to deliver the idea toward the discussion study by the other participants. Directive speech acts were produced to ask the question, request for answer the question, suggestion, command, and invite in the discussion. Last, expressive speech acts presently as the most dominant speech acts in the discussion study including the word thanking, appreciating, agreeing, praising, and apologizing. Penelitian ini membahas tentang klasifikasi tindak tutur yang dihasilkan oleh mahasiswa dalam studi diskusi online di Jurusan Bahasa Inggris di Universitas Negeri Padang, Indonesia. Penelitian ini dilakukan dengan menggunakan pendekatan kualitatif yang menggambarkan penggunaan tindak tutur mahasiswa dalam interaksi mahasiswa ke mahasiswa, dan mahasiswa ke dosen. Terdapat dua puluh empat mahasiswa yang terlibat dalam diskusi yang berpartisipasi sebagai sumber data. Insturmen yang digunakan peneliti adalah lembar observasi yang didukung oleh rekaman video. Rekaman video lalu ditranskip kedalam teks yang nantinya akan diuji oleh peneliti terkain tindak tutur yang dihasilkan siswa. Temuan penelitian menunjukkan bahwa terdaoat empat jenis tindak tutur yang dilakukan oleh siswa pendidianbahasa Inggris, yaitu asertif, direktif, ekspresif dan komisif, sedangkan tindak tutur deklaratif tidak digunakan oleh siswa. Tindak tutur yang paling sering dilakukan oleh siswa adalah tindak tutur asertif dengan total 7 ucapan, direktif dengan total 9 ucapan, dan komisif dengan total 10 ucapan. Tindak tutur asertif dilakukan untuk mendemonstrasikan materi diskusi oleh penyaji dan digunakan untuk menyampaikan gagasan terhadap kajian diskusi oleh peserta lain. Tindak tutur direktif diproduksi untuk mengajukan pertanyaan, meminta jawaban atas pertanyaan, saran, perintah dan mengajak dalam diskusi. Terakhir, tindak tutur ekspresif hadir sebagai tindak tutur yang paling dominan dalam kajian diskusi meliputi kata berterima kasih, menghargai, menyetujui, memuji, dan meminta maaf. Â